Art and informatics: key elements for a new school "grammar" - Andrea de Farias Castro (Universidad Autónoma de Madrid, 2015)
A new scientific approach points to the idea of the creation of order by disorder, indicating the convergence of two cultures, human and scientific, starting a new era of knowledge. We believe it is possible, and appropriate, for the school to consider the prerogative that, in order to adequately fulfill its current role as an interesting place where formal education can be obtained, it will be necessary to incorporate the notion that "learning is going from uncertainty to a provisional certainty that gives rise to new discoveries and new syntheses ". After all, according to Vygotsky, the human mind provokes concepts from experiences that go beyond the search for permanent truths, since it is constantly in process.